Ownership versus control : fault lines in director-shareholders relationship - special reference to Malaysian family business - Abd Ghadas, Zuhairah Ariff; Hassan, Halyani (UUM Press, 2011)
he structure of family business is unique compared to the non-family business as it combines three elements, namely, family relationships, composition of owners and management structure under the name of the business. This distinctive attribute often give rise to governance issues. Under the conventional concept of corporate governance, directors should act in the best interest of the shareholders. In doing so, the directors’ action is governed by certain rules which specify their duties and these rules are relevant to the shareholders with respect to their rights. Although there are laws which govern the relationship between the directors and shareholders, in certain circumstances there are some latent problems. These hidden problems can be identifi ed as the fault lines in the relationship between directors and shareholders. This article discusses the issues pertaining to fault lines which may arise in a family business due to the complex and overlapping structure between directors and shareholders in a family business. Research methodology applied in this research is mainly doctrinal analysis.